REGULASI DAN KEBIJAKAN UNTUK EKONOMI SIRKULAR: TINJAUAN LITERATUR GLOBAL DAN LOKAL - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
The circular economy has emerged as an important paradigm in global efforts towards sustainable development. This study presents a comprehensive review of the current literature on circular economy regulations and policies at the global and local levels. Key findings indicate a significant increase in the adoption of circular economy policies worldwide, but with substantial variations in approaches and levels of implementation. This study identifies several key factors influencing policy success, including supportive legal frameworks, economic incentives, multi-stakeholder collaboration, and technological innovation. Major challenges identified include a lack of standardisation, gaps in implementation between national and local policies, and the need for better metrics to measure policy impact.